Konsep dan Penerapan Takwil Muhammad Quraish Shihab dalam Tafsir Al-Mishbah - Junaedi, Dedi (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2017)
The problem of taâ€™wÄ«lÂ in Qurâ€™anic studies is regarded as one of the controversial issues. It requires a holistic study on taâ€™wÄ«l. Some scholars still criticized the takwil as a method of understanding of the Qurâ€™an. Some qurâ€™anic commentators who did not give their commentaries will say AllÄhu aâ€™lamu bi murÄdihi (It is only God who knows the meaning). However, another commentator did not agree with them. They then use taâ€™wÄ«l. One of qurâ€™anic scholars who used taâ€™wÄ«lÂ is Muhammad Quraish Shihab. He is an Indonesian qurâ€™anic commentator. One of his works is â€˜Tafsir al-Mishbahâ€™. It can be called as a remarkable work of tafsir. He used the different method of qurâ€™anic interpretation. He has a deep linguistic approach and comprehensive understanding. He also uses an approach of tafsÄ«r bi al-raâ€™yiÂ that also used the traditional source as well.